The Pandemic Real Challenges In Hotel Industry: Managing Emotions And Mental Health Of Employees - Farah Laili Muda @ Ismail; Anita Ismail (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.